Development of Module Teaching Materials Writing Short Texts of Literacy-Based for Students of Senior High School Parulian 1, Medan, Indonesia - Kasman Supriadi; Khairil Ansari; Abdurahman Adisaputera (BIRCU, 2019)
The aims of this study is to find out the development of module teaching material of writing short story of literacy based in Senior High School Parulian 1 medan. The research method of this study is qualitative research. The result show that The development of module teaching materials is carried out by determining the title, objectives, material selection, framework preparation, and collection of relevant materials with short story writing material and the techniques used in writing short stories. In addition, to assess the feasibility of the product being developed, validation tests were conducted involving expert lecturers, and Indonesian language teachers, as well as limited student testing. Feasibility assessment of this module includes 4 aspects, namely aspects of content / material, presentation, language, and graphics.